Identifying Indonesia-Uruguay Bilateral Trade Opportunities:A Revealed Comparative Advantage Approach - A Sulthon Sjahril Sabaruddin; Riris Rotua Sitorus (UBL, 2013)
This paper attempts to identify and analyze the Indonesia-Uruguay bilateral trade opportunities based on their respective export competitiveness. The analysis uses the Revealed Comparative Advantage Index for year 2012 obtained from World Integrated Trade Solution (WITS). The paper reveals that there are still opportunities for both countries to further strengthen bilateral trade relations.Based on the RCA Index analysis, the paper finds that in general both countrieshave exported their commodities based on their comparative advantage, but however both countries current exports still do not reflect their potentials as most of the top ten commodities with the strongest comparative advantage are still not yet able to penetrate the both sides market. This study suggests both countries should remove trade barriers starting by providing access for the top 10 commodities with the strongest comparative advantage to penetrate in both countries. This step could be a stepping stone towards further intensifying bilateral trade relations.